PEMODELAN PEMANTAU PERSEDIAAN BARANG DAN PEMESANAN BARANG BERBASIS JARINGAN KOMPUTER - Nudroho, Djoko Hari; Harlianto T., Harlianto T.; Fredy, Fredy (Universitas Tarumanagara, 2007)
Modeling scheme to observe stock and to order goods based on computer network. Function to lighten stock observation at store/warehouse, to reduce stock failure and to facilitate purchase order from store/warehouse to supplier.